Teacher Efforts to Instill Character Values in Learning - Islahiyah Islahiyah; Ika Lis Mariatun; Yusrianto Sholeh (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to describe the efforts of teachers to instil character values ​​in economics lessons for class XI at MA Darul Ulum Tlagah Galis Bangkalan. This study used a descriptive qualitative research method. The subjects in this study were economics teachers, school principals and class XI students. The instrument in this research is the researcher himself. Data collection techniques using observation, interviews and documentation. Data analysis techniques include three activities, namely data reduction, data presentation and conclusion. The results of this study indicate that efforts to instil character education values ​​in economics learning for class XI at MA Darul Ulum Tlagah Galis, Bangkalan Regency, have been going well. This has been seen from the lesson plans for economics teachers, which include character education values ​​such as religion, honesty, discipline, responsibility, caring, politeness, responsiveness, and proactive. The efforts made by the teacher to instil character values ​​in the learning process are prepared in a planned manner by school institutions using the teaching stages through the planning stages, implementation stages, and evaluation stages. Then the teacher's efforts to instil character values ​​in economics learning inside and outside the classroom are carried out properly, starting from the methods used during learning, reading prayers before entering class, followed by Duha prayers and Duhur prayers in congregation.